EFEKTIVITAS IMPLEMENTASI STRATEGI ENJOYABLE LEARNING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR BAHASA INGGRIS PERMULAAN PESERTA DIDIK SEKOLAH DASAR - Bayu, Gede Wira (Jurnal Ilmiah Sekolah Dasar, 2019)
This research is based on the low learning outcomes of English language learning in elementary schools especially after the implementation of the 2013 curriculum where the time of learning English is much reduced from 4 hours a week in the Education Unit Level Curriculum (KTSP) to only 2 hours a week in the 2013 curriculum. To overcome these problems, it is considered important to implement the Audio-Visual Media-Assisted Enjoyable Learning Strategy. Pre-experimental research One Group Pretest-Posttest Design. The subjects in this study were grade 2 students in 8 elementary schools who had just implemented the 2013 curriculum in the 2018/2019 learning year in Buleleng sub-district. The data in this study were obtained by interview methods and field notes. With the random sampling technique, the subjects of this study were selected, namely grade 2 students in SD N 5 Banyuning, amounting to 27 students as a control group, and second grade students in SD N 2 Banjar Tegal, amounting to 25 students as the experimental group. Based on the results of the calculation of the tcount of 5.34. To find out the value of t table with degrees of freedom (dk) = 44 significance level (α) = 0.05 obtained the value of t table = 2.023. By comparing the value of tcount and ttable, the ratio of tcount> ttable is obtained, meaning H0 is rejected and Ha is accepted. And from the average, it was known that the experimental group was 20.86 and the control group was 15.18. This means experiment> control group. Thus, the Enjoyable Learning strategy assisted by audio visual media has a significant effect on the learning outcomes of English in Class II SD students in the 2013 Curriculum Application in the District of Buleleng, Buleleng Regency, Academic Year 2018/2019.